Human Resources Development Strategy In Baitul Mal Watamwil An-Najah, Pekalongan District - Sri Hartono, Bambang; Rohmah, Farida; Budiharjo, Arif (Velocity: Journal of Sharia Finance and Banking, 2021)
This study aims to describe the human resource development strategy, analyze the internal and external environment of the business, and compile a plan for the development of aspects of human resources in Baitul Mal Wa Tamwil An-Najah. This research is a field research and the approach used in this study is a qualitative method. Conducted at Baitul Mal waTamwil An-Najah Pekalongan from July to December 2017. Data collection techniques in this study were through observation, interviews, and documentation. This study uses descriptive analysis techniques that aim to provide an overview of the research subject based on the data and variables obtained. In addition, there is also a SWOT analysis to provide several recommendations for companies in developing their employees to achieve company goals. Based on the research results, it is known that the human resource development strategy in Baitul Mal waTamwil An-Najah, Pekalongan Regency through orientation, training and education programs, as well as career development. Through the SWOT analysis, points of development plans related to aspects of human resources in Baitul MalwaTamwil An-Najah were obtained which could serve as recommendations and reminders for the company. The development plan is built with the SO (Strength-Opportunity) strategy, the WO (Weakness-Opportunity) strategy, the ST (Strength-Threats) strategy, and the company's WT (Weakness-Threats) strategy. This analysis is expected to improve human resource development strategies.